Fortis Femina: Artemisia Gentileschi’s Treatment of Cleopatra and Seventeenth-Century Italian Art - (:unkn) unknown (My University, 2023)
Cleopatra is a historical figure with mythical fame; she has captivated the attention of artists over centuries and millennia. Two common themes of the myriad portrayals of her infamously purported death by asp are her sexualized figure and the masculine identities of the majority of artists. But, what about female artists? How did they depict Cleopatra? Did they similarly sexualize her figure? This paper seeks to partially address these previously little-answered questions by using the representative example of Artemisia Gentileschi’s ca. 1635 Cleopatra painting, which has not been as thoroughly examined as many of her other works featuring heroic or strong women. The primary focus of this work is to compare and contrast Artemisia’s illustration of Cleopatra’s demise with those created by her male contemporaries, such as Guido Reni, who was a celebrated artist in seventeenth-century Italy. The evidence described in this work suggests that Artemisia indeed infuses her Cleopatra painting with a feminine perspective that her male contemporaries are unable to adopt. Ultimately, the ca. 1635 work successfully showcases Artemisia’s awareness of the sexualized Cleopatra as an archetype and rather than embracing it, creates a new narrative.
Keywords: Artists; Cleopatra; Italy; Women